A preliminary evaluation of bio-based epoxy resin hardeners for maritime application. (2017) - Benega, Marcos A.G.; Raja, Robert; Blake, James I.R.
Abstract: A screening of different hardeners derived from cashew nut shell liquid (CNSL) was performed; they were compared to a conventional hardener in an epoxy resin system for composite production by infusion process. All samples were submitted to different post-curing processes before tensile strength and moisture uptake were evaluated. It was observed that the use of CNSL hardeners produced cured epoxies similar in Young's Modulus (YM) to the conventional hardener with a lower moisture uptake however, the hardeners resulting in a low YM had a marked reduction in moisture uptake. Studies of the post-curing process showed that the moisture uptake of the conventional system can be improved but, depending on the temperature applied, the process can be detrimental to the CNSL hardeners, provided that moisture uptake was increased after post-curing. The results indicate that biobased content can be introduced to a conventional epoxy resin system by replacing the conventional hardener commonly used by a sustainable one derived from cashew nut shell liquid with an additional moisture uptake reduction.